A review of Chinese tribe Achilini (Hemiptera: Fulgoromorpha: Achilidae), with descriptions of Paracatonidia webbeda gen. & sp. nov. - Long, Jian-Kun; Yang, Lin; Chen, Xiang-Sheng (Zootaxa, 2015)
Planthoppers of the tribe Achilini (Hemiptera: Fulgoromorpha: Achilidae) from China, are reviewed. A key to the three genera of Chinese Achilini is given. A new genus and species of the tribe from southwestern China: Paracatonidia webbeda gen. & sp. nov., is described. A new genus and species record for China, Cixidia kasparyani Anufriev, is also given.